Beyond Conventional Responses: Comparative Land Defense Strategy Against the Hybrid-Separatist Threat In Indonesia and the Philippines - Royhan Asshiddiky (Manunggal Halim Jaya, 2026)
Contemporary separatism no longer works in one domain: armed violence, narrative building in the international arena, and exploitation of development gaps as a recruitment base operates simultaneously. Defense responses that target only the physical domain experience structural deficits that cannot be overcome by increasing combat capacity. Basically, this study aims to identify patterns of failure to adapt land defense doctrines in the face of hybrid-separatist threats in Indonesia and the Philippines, as well as formulate the most institutionally realistic transformation prerequisites. This study uses a comparative case study design with the logic of most-similar systems and process tracing methods, with data sourced from official doctrinal documents, International Crisis Group reports, IISS, SIPRI, and relevant academic literature. The results of the study show that the TNI-AD and AFP face a similar pattern of structural failure even though they are taken through different paths: The Regional Command holds the architectural potential of community-based early detection that has never been connected to a multi-domain threat management system, while the Bayanihan IPSP offers a conceptually robust whole-of-nation framework but is not successfully operationalized consistently and does not have an adaptation mechanism to shifting actors partial post-peace threat. The study concludes that doctrinal transformation (not the addition of resources) is a key prerequisite for successful strategic adaptation, and that the most realistic solution lies in expanding the scope of doctrine in existing systems, rather than establishing new institutional structures.